Curing and mechanical properties of bio-based hybrid thermoset resins from unsaturated polyester and acrylated epoxidized palm oil - Fakhari, Alireza (2015)
In this study a series of green thermoset resins have been produced from blending acrylate epoxidized palm oil (AEPO) and unsaturated polyester (UPE). The UPE/AEPO ratio was changed between 90/10 and 70/30 wt%. The curing behavior and morphology of hybrid systems were investigated by differential scanning calorimeter (DSC) and Scanning electron microscope (SEM). Moreover, studies on mechanical properties were performed by tensile and flexural tests. The results revealed that, these green thermoset resins exhibit thermo mechanical properties comparable to those of commercial unsaturated polyesters.